2023
DOI: 10.3390/ijms24076638
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated Gold Nanoparticles Conjugated with siRNA: Complexes Formation and Cytotoxicity

Abstract: Drug delivery systems such as dendrimers, liposomes, polymers or gold/silver nanoparticles could be used to advance modern medicine. One significant pharmacological problem is crossing biological barriers by commonly used drugs, e.g., in the treatment of neurodegenerative diseases, which have a problem of the blood-brain barrier (BBB) restricting drug delivery. Numerous studies have been conducted to find appropriate drug carriers that are safe, biocompatible and efficient. In this work, we evaluate pegylated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…AuNPs find significant applications in nanomedicine, particularly in biosensor labeling, bioimaging, drug delivery systems, and phototherapeutic roles. (12,13,15,21) Recent research have focused on the development of affordable biocompatible NPs that can be employed in clinical trials. (7) In this scenario, AuNPs stand out because of their high biocompatibility and ability to be used in different applications.…”
Section: ❚ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AuNPs find significant applications in nanomedicine, particularly in biosensor labeling, bioimaging, drug delivery systems, and phototherapeutic roles. (12,13,15,21) Recent research have focused on the development of affordable biocompatible NPs that can be employed in clinical trials. (7) In this scenario, AuNPs stand out because of their high biocompatibility and ability to be used in different applications.…”
Section: ❚ Discussionmentioning
confidence: 99%
“…(10) In addition to being stable, simple to manufacture, controllable in size, and straightforward for surface functionalization, these NPs also present strongly enhanced optical properties and high biocompatibility for in vivo studies. (11) The utilization of AuNPs has thus distinguished itself in a number of applications, serving as promising carriers for different biomolecules, such as drugs, therapeutic proteins, DNA, or RNA, (12,13) in addition to acting as phototherapeutic and tumor detection agents. (13)(14)(15)(16) One of the more feasible options for enhancing the medical properties of AuNPs is PEGylation, which involves coating NPs with PEG, a biopolymer that is affordable, versatile, and FDA-cleared.…”
Section: ❚ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 20 For instance, doxorubicin can be efficiently attached to PEG-coated AuNPs for targeted cancer cell treatment. 21 Okła E. 22 and colleagues used PEG-AuNPs (AuNP14a and AuNP14b) coupled with therapeutic siRNA targeting the Alzheimer's disease gene (APOE4). The conjugated complexes exhibited low cytotoxicity, providing a foundation for further research into the use of gold nanoparticles in nucleic acid delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Elżbieta Okla et al harnessed this ability of AuNPs and modified them through Polyethylene Gylcol (PEG)ylation to improve the central nervous system (CNS) delivery of a AuNP/APOE small interfering Ribonucleic Acid (siRNA)formulation for Alzheimer’s disease treatment. Additionally, they showed that these AuNPs/siAPOE4 complexes demonstrated significantly lower cytotoxicity in human brain endothelial cells than free nanoparticles, demonstrating the safety and tolerability of this novel nanotherapeutic formulation [ 9 ].…”
mentioning
confidence: 99%